1996
DOI: 10.1016/0014-5793(95)01512-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta cell granule components on human islet amyloid polypeptide fibril formation

Abstract: Formation of amyloid-like fibrils in a solution of human islet amyloid polypeptide (hIAPP) with and without the presence of other IS-cell granule components was studied in vitro. Insulin at less than equimolar concentration strongly inhibited hIAPP fibrillogenesis. Proinsulin had a weaker inhibitory effect while C-peptide, Ca 2+ and Zn 2÷ each individually enhanced fibril formation. C-peptide combined with Ca 2+ had an inhibitory effect. Since IAPP was found almost exclusively in the halo fractions of isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
205
3
13

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(229 citation statements)
references
References 21 publications
8
205
3
13
Order By: Relevance
“…Indeed, because the simple addition of h-IAPP to islets causes cell-to-cell disruption, it might be questioned, what are the mechanisms present in healthy islets that prevent recently secreted h-IAPP from forming toxic oligomers? One possible factor is the associated high insulin content discharged from the insulin secretory vesicle since insulin inhibits h-IAPP amyloid formation in an aqueous environment (37). Also, the acidic pH in the secretory vesicle may be sufficient in the immediate site of exocytosis to prevent h-IAPP oligomerization (38).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, because the simple addition of h-IAPP to islets causes cell-to-cell disruption, it might be questioned, what are the mechanisms present in healthy islets that prevent recently secreted h-IAPP from forming toxic oligomers? One possible factor is the associated high insulin content discharged from the insulin secretory vesicle since insulin inhibits h-IAPP amyloid formation in an aqueous environment (37). Also, the acidic pH in the secretory vesicle may be sufficient in the immediate site of exocytosis to prevent h-IAPP oligomerization (38).…”
Section: Discussionmentioning
confidence: 99%
“…If our hypothesis is correct, i.e., if hIAPP fibril growth causes membrane damage, then one would predict that inhibition of hIAPP fibril growth would also inhibit hIAPP-induced membrane leakage. To test this, we have chosen insulin as a biologically relevant, potent inhibitor of hIAPP fibril formation (29)(30)(31). The mechanism of inhibition of hIAPP fibril formation by insulin is most likely related to strong binding of the insulin B-chain to hIAPP (32).…”
Section: Seeding Reduces the Lag Time Of Hiapp-induced Membrane Damagementioning
confidence: 99%
“…5 Note that amylin aggregates are commonly found as amyloid deposits in pancreatic islets from diabetic patients. 6 While the causative relationship between aggregation of human amylin peptide and Type II diabetes is not known, it has been established that aggregates of human amylin can induce apoptopic cell-death of the insulin producing β-cells. 2 Perhaps more importantly, recent experiments have shown that the main toxic species are the pre-fibrillar, early stage oligomers of the peptide.…”
Section: Introductionmentioning
confidence: 99%